1995
DOI: 10.1002/jbm.820290407
|View full text |Cite
|
Sign up to set email alerts
|

Mediator interactions in macrophage/particulate bone resorption

Abstract: The purpose of this study was to examine the mechanism by which mediators released from macrophages exposed to cement particles may interact with cells in bone to ultimately lead to bone resorption. Macrophages were exposed to cement particles, and then this conditioned medium was exposed to rat calvarial bones in vitro. The macrophage conditioned medium contained increased levels of tumor necrosis factor, but not interleukin 1 or prostaglandin E2. Exposure of this medium to the calvaria led to release of pros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
47
0
1

Year Published

1996
1996
2000
2000

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 31 publications
5
47
0
1
Order By: Relevance
“…Those with a TiAlV cemented prosthesis showed a significant increase in levels of IL-1␤ and also had the highest levels of IL-6. These data agree with the results of other authors, who showed that TiAlV 7,18,19 and polymethylmethacrylate particles 20 in vitro induced the release of inflammatory cytokines in monocyte/macrophages. The highest cytokine concentrations were observed in the group of patients treated with NSAIDs.…”
Section: Discussionsupporting
confidence: 83%
“…Those with a TiAlV cemented prosthesis showed a significant increase in levels of IL-1␤ and also had the highest levels of IL-6. These data agree with the results of other authors, who showed that TiAlV 7,18,19 and polymethylmethacrylate particles 20 in vitro induced the release of inflammatory cytokines in monocyte/macrophages. The highest cytokine concentrations were observed in the group of patients treated with NSAIDs.…”
Section: Discussionsupporting
confidence: 83%
“…7,8,23 In prior studies from this laboratory, conditioned media obtained from macrophages exposed to PMMA particles were able to stimulate 45 Ca release from radiolabeled calvaria even without an additional osteoblast contribution. 18 In addition, in previous studies using this cell line, TNF-␣ was identified as being the principle mediator released from macrophages exposed to PMMA particles which was necessary to stimulate 45 Ca release from labeled calvaria. 20 It is speculated that the difference between the boneresorbing ability of media obtained from macrophages 45 Ca release.…”
Section: Discussionmentioning
confidence: 96%
“…This finding is consistent with the results of other studies in which the mechanism by which particulate exposure to macrophages leads to mediator release and osteoclast recruitment is dependent upon the presence of osteoblasts. 16,18,24,25 Exposure of macrophages to cobalt chromium particles was toxic, as reflected by release of LDH. This is also consistent with the results of Haynes et al, 22 who also found significant toxicity associated with these particles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Examples of these are prototypes of inflammatory cells such as peripheral blood monocytes, lymphocytes, and fibroblastic cells (Rae et al, 1979;Goldring et al, 1990;Giant et al, 1993;Horowitz et al, 1991Horowitz et al, , 1995Haynes etal, 1993;Frondoza etal, 1994;Shanbhag etal, 1995;Gonzales etal, 1996). Cells retrieved from tissues or blood which are maintained in short-term culture for immediate use are thought to most closely express their original tissue characteristics or "phenotype."…”
Section: Effect Of Prosthetic Wear Debris On Macrophages Fibroblastsmentioning
confidence: 99%